After Covid‐19, the US statistical system needs to change. Issue 4 (29th July 2020) - Lane, Julia
Abstract : Julia Lane calls for a new, more democratic, public data infrastructure Abstract : Julia Lane calls for a new, more democratic, public data infrastructure.